Stability and Boundedness of Solutions of Nonlinear Third Order Differential Equations with Bounded Delay - Özdemir, Abdulhamit; Korkmaz, Erdal (My University, 2022)
In this paper, we investigate the boundedness and uniformly asymptotically stability of the solutions to a certain third order non-autonomous differential equations with bounded delay. By constructing a Lyapunov functional, sufficient conditions for the stability and boundedness of solutions for equations considered are obtained. We used an example to demonstrate the feasibility of our results. The results essentially improve, include, and complement the results in the literature.
Keywords: Boundedness; Delay differential equations; Lyapunov functional; Stability; Third order